Randomised controlled trial evaluating the effects of screening and referral for social determinants of health on Veterans' outcomes: protocol. Issue 9 (23rd September 2022) - Gurewich, Deborah; Kressin, Nancy; Bokhour, Barbara G; Linsky, Amy M; Dichter, Melissa E; Hunt, Kelly J; Fix, Gemmae M; Niles, Barbara L
Abstract : Introduction: Health policy leaders recommend screening and referral (S&R) for unmet social needs (eg, food) in clinical settings, and the American Heart Association recently concluded that the most significant opportunities for reducing cardiovascular disease (CVD) death and disability lie with addressing the social determinants of CVD outcomes. A limited but promising evidence base supports these recommendations, but more rigorous research is needed to guide health care-based S&R efforts. Funded by the Veteran Health Administration (VA), the study described in this paper will assess the efficacy of S&R on Veterans' connections to new resources to address social needs, reduction of unmet needs and health-related outcomes (adherence, utilisation and clinical outcomes). Methods and analysis: We will conduct a 1-year mixed-methods randomised controlled trial at three VA sites, enrolling Veterans with CVD and CVD-risk. 880 Veterans experiencing one or more social needs will be randomised within each site (n=293 per site) to one of three study arms representing referral mechanisms of varying intensity (screening only, screening and provision of resource sheet(s), screening and provision of resource sheet(s) plus social work assistance). For each Veteran, we will examine associations of unmet social needs with health-related outcomes at baseline, and longitudinally compare the impact of each approach on connection to new resources (primary outcome) and follow-up outcomes over a 12-month period. We will additionally conduct qualitative interviews with key stakeholders, including Veterans to identify potential explanatory factors related to the relative success of the interventions. Ethics and dissemination: Ethics approval was obtained from the VA Central Internal Review Board on 13 July 2021 (reference #: 20-07-Amendment No. 02). Findings will be disseminated through reports, lay summaries, policy briefs, academic publications, and conference presentations. Trial registration number: NCT04977583 .